2013
DOI: 10.1093/mnras/stt2027
|View full text |Cite
|
Sign up to set email alerts
|

Nova multiwavelength light curves: predicting UV precursor flashes and pre-maximum halts

Abstract: The dramatic brightenings of classical novae have yielded rich data sets of detailed light curves. Modelling these light curves is a challenge for any theory of classical novae. We have used our extended grid of nova outburst calculations to predict the luminosities of erupting novae expected in three electromagnetic bands-the visual, the near UV and the X-ray. Our models predict and explain many features of novae before eruption, as well as detailed characterizations of nova outbursts and post-nova declines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 28 publications
(34 reference statements)
5
58
1
Order By: Relevance
“…Thus the two peaks are consistent with being such excursions from the general upwards trend, rather than being defined by dips that interrupt the rise. The combination of the change relative to the uncertainties and the deviation from what one would expect from backwards extrapolation of the rise, allows us to be confident that they can be reasonably described as PMHs as modelled by Hillman et al (2014).…”
Section: Pre-maximum Haltsmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus the two peaks are consistent with being such excursions from the general upwards trend, rather than being defined by dips that interrupt the rise. The combination of the change relative to the uncertainties and the deviation from what one would expect from backwards extrapolation of the rise, allows us to be confident that they can be reasonably described as PMHs as modelled by Hillman et al (2014).…”
Section: Pre-maximum Haltsmentioning
confidence: 93%
“…The cadence is around 40 min, making these the highest time-resolution observation of this phase to date. We discuss the rise phase, including the PMHs, in the context of the models of Hillman et al (2014). We also contrast the post-maximum behaviour with much slower Classical Novae (CNe) and suggest that the empirical split in this behaviour between slow and fast novae is in part a function of the typical one day sampling of the light-curves.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This tendency agrees with our results. Hillman et al (2014) showed evolutionary change in the effective temperature of nova outbursts with the OPAL opacities. Their Figure 3 shows an X-ray flash duration (defined by log T eff (K) > 5.5) of a few hours for a 1.4 M ⊙ WD with a mass accretion rate of 10 −8 M ⊙ yr −1 .…”
Section: Slow Evolution After X-ray Flashmentioning
confidence: 95%
“…Although in standard models novae are thought to be powered directly by the energy released from nuclear burning (e.g. Hillman et al 2014), growing evidence suggests that shock interaction plays an important role in powering nova emission across the electromagnetic spectrum. Evidence for shocks includes multiple velocity components in the optical spectra (e.g.…”
Section: Introductionmentioning
confidence: 99%